Positive Solutions to n-Order Fractional Differential Equation with Parameter - Jing-jing Tan; Cong Tan; Xueling Zhou (Journal of Function Spaces)
By employing the properties of the sum operators, we investigate the solutions of the n-order fractional differential equations multiple point boundary value problem (in short BVP) with the boundary conditions contains a parameter. We not only obtain the existence and uniqueness of solutions about this BVP but also construct an iterative scheme to approximate the solution which is important for practical application. An example is given to demonstrate the validity of our main results.